(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aims to identify the forms of bank financing provided by traditional banks, and to measure the impact of internal factors on the volume of private banking investment. The research is based on the descriptive analytical approach, and multivariate analysis (standard models) was adopted to discover the impact of factors on the size of private banking employment. The E-VIWS program was used to extract and show the results and test the hypotheses. The financial statements published from 2010 to 2021 were used Among the most important results: There is a positive, statistically significant effect of the debt ratio (DPOS) on the banking investment rate, and the most influential indicators were for the equity ratio (EOA) and the rate of return on equity (ROE), and there is a negative, statistically significant effect for the rate of return on assets. (ROA) on the bank investment rate, while there is no statistically significant effect for the liquidity ratio (DOCA) and the shareholder equity ratio of total deposits (EOD) on the bank investment rate.